Макротеоретична етимологія фіскальних правил - Козюк, Віктор; Kozyuk, Victor (ТНЕУ, 2015)
Доведено, що етимологічно запровадження фіскальних правил коріниться у положеннях нової класичної макроекономіки. Показано, що прямі аналогії з динамічною інконсистентністю монетарної політики є обмеженими внаслідок відмінної природи реалізації владних повноважень урядом і центральним банком. Стверджується, що фіскальні правила є більш транспарентним критерієм ідентифікації дій політиків, особливо у випадках, коли альтернативні макротеоретичні концепції допускають суттєві відмінності в оптимальних траєкторіях державного боргу. Показано, що фіскальні правила можуть ефективно впливати на обмеження фіскального опортунізму, хоча і не гарантують повне його усунення. The macroeconomic policy structural reforms that have being taking place during last 20 years show fundamental tendency to enhance institutional mechanisms of policy oriented on stability, efﬁ ciency and decrease vulnerability to external shocks. Fiscal policy regime switch basing on rules backgrounds often followed successful reforms of central banks. Large difference between political nature of monetary and ﬁ scal decision-making is looked as a important driving force of additional macroeconomic considerations in direction to ﬁ scal discipline. New sources of ﬁ scal vulnerability in the long-run (aging, contingent liabilities, tax competition etc…) are looked as important drivers of ﬁ scal discipline institutional protection. Empirical results show that there are some relations between ﬁ scal rules design and ﬁ scal discipline, but sometimes rule-based ﬁ scal policy is not a guarantee against debt vulnerability. European debt crisis is good example of ﬁ scal rules fragility. In some case, numerical rule for debt to GDP limit may be frustrated though lost motivation to decrease debt level down from committed point opening the door for loosening ﬁ scal ﬂ exibility during trouble times. So, macroeconomic validation of ﬁ scal rules is background for rational choice to have more disciplined deﬁ cit policy. Aside of applyability of dynamic inconsistency approach on ﬁ scal rules, it is clear that differences between monetary and ﬁ scal policy provide additional considerations about ﬁ scal vulnerabilities. It is highlighted that most differences between monetary and ﬁ scal policy from rules-based policy approach related to: short- and long-term effects of ﬁ scal and monetary responds; differences in lags length; globalization inﬂ uence on numerical target; possibilities to manipulate with numerical target; understanding what is efﬁ ciency of policy and what is outcome of efﬁ cient policy etc. Dynamic inconsistency theory shows fragility on the level of decision making. But social incentives to have stable ﬁ scal environment should be based on understandings of risks for macroeconomic stability from unstable debt path and discretion over deﬁ cits. Market discipline fail is important driving force why ﬁ scal policy should be restrained by rules. The more wide approach on ﬁ scal policy efﬁ ciency is the more fragile is incentive structure on the level of decision making. Fiscal rules in this respect are viewed as important part of compensation of market fails and political opportunism. Wider understanding of what is efﬁ cient ﬁ scal policy relative to monetary policy is viewed as prominent validation of why ﬁ scal policy should be rules-based.
Macrotheoretical etymology of ﬁ scal rules
Keywords: фіскальні правила; державний борг; бюджетний дефіцит; фіскальна політика; макроекономіка; ﬁscal rules; public debt; budget deﬁcit; ﬁscal policy; macroeconomics